The correlated evolution of social competence and social cognition. (7th August 2019) - Varela, Susana A. M.; Teles, Magda C.; Oliveira, Rui F.
Abstract: Knowing which of correlated traits are more strongly targeted by selection is crucial to understand the evolutionary process. For example, it could help in understanding how behavioural and cognitive adaptations to social living have evolved. Social competence is the ability of animals to optimize their social behaviours according to the demands of their social environment. It is a behavioural performance trait that expresses how well a whole organism performs complex social tasks, such as choosing mates, raising offspring, participating in dominance hierarchies, solving conflicts or forming social bonds. Non‐social competence, on the other hand, is the ability of animals to optimize their non‐social behaviours according to the demands of their non‐social environment, such as finding food or avoiding predators. Social and non‐social cognition are correlated lower‐level traits of social and non‐social competence, respectively, encompassing the underlying psychological and neural mechanisms of behaviour that allow animals to acquire, encode, store and recall information about their social and non‐social environments. Here, we employ the theoretical framework that selection acts on performance traits first and on lower‐level traits only secondarily, to propose a new approach to the study of the evolution of social cognition. We hypothesize that when selection favours social competence, the cognitive system becomes more adapted to the social domain, making species biased for social information, and increasing their degree of sociality. The opposite can happen when selection favours non‐social competence. The level of specialization that the cognitive system can attain depends on whether social and non‐social competence are correlated with the same cognitive lower‐level traits. This in turn will determine whether species will evolve a type of social cognition that is general—that contributes with cognitive abilities that can be used in both social and non‐social environments—or modular—that contributes with cognitive abilities that are specific to the social environment. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.